THE RELATIONSHIP OF STUDENTS’ ATTITUDES TOWARDS ART AND SCHOOL CLIMATE ON ARTS LEARNING OUTCOMES - patonah, patonah; Hidayat, Sholeh; Aisyah, Siti (JPSD (Jurnal Pendidikan Sekolah Dasar), 2025)
Good student learning outcomes are essential for achieving national educational goals, including in art subjects at the elementary school level, which are integral to implementing an independent curriculum. This research examines the correlation between students’ attitudes towards art and the school climate with students’ art learning outcomes to provide valuable insights for improving the educational process. The research aims to explore the extent to which these variables are interconnected in influencing student learning outcomes. A correlational quantitative approach was used through a survey involving 129 respondents from 4th to 6th grades at SD Negeri Kampung Bayur, East Sepatan District, Tangerang Regency. Data were collected using a questionnaire to test the significance of the relationship between the variables. The findings reveal a significant positive relationship between students’ attitudes towards art 18.5% and school climate 63.8% with students’ learning outcomes, with a combined positive correlation of 36.2%. These results suggest that teachers, as key facilitators of student learning, should foster a positive school climate to enhance students’ learning experiences and outcomes